Thailand : Staff Report for the 2012 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
Thailand is recovering from a challenging year marked by natural disasters of historic magnitude. This 2012 Article IV Consultation highlights that positive signs of a recovery are already under way with sharp improvements seen in high frequency indicators since December 2011. Executive Directors have commended the Thai authorities for their policy response to last year's floods, which propelled the strong recovery under way. Directors have also supported the authorities' ambitious reform agenda aimed at promoting more inclusive growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet